(untitled) (Journal of Parents and Teachers, 2014)
In this article we describe two of the most important results in Astronomy in the last two decades, namely, the detection of extrasolar planets or exoplanets (i.e. planets orbiting stars other than the Sun), and the discovery that the current expansion rate of the Universe is larger than it was in the past. The first result is the initial step to answer the question of whether we are alone in the Universe. The second one implies that the Cosmology –the discipline studying the origin and evolution of the Universe- must make a deep revision of some foundations that were considered solid so far.